2014
DOI: 10.1111/joim.12262
|View full text |Cite
|
Sign up to set email alerts
|

Statin use reduces the risk of dementia in elderly patients: a nationwide data survey and propensity analysis

Abstract: Objectives. The objective of this study was to examine the association between the use of statins and the risk of newly diagnosed dementia in an elderly population.Design, setting and participants. Random samples of 1000 000 individuals covered by the National Health Insurance in Taiwan were included in the analysis. All participants were 65 years or older without dementia and either did or did not start treatment with statins from 1 August 1997 to 31 December 2010. Patients with established dementia before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
(27 reference statements)
4
22
0
Order By: Relevance
“…10 In a nationwide data survey in Taiwan, Wu et al reported a significant protective effect for individuals who took statins for more than 830 days. 36 In our study, for the continuous statin users, the average time from baseline until diagnosis was 5.8 years.…”
Section: Discussionmentioning
confidence: 70%
“…10 In a nationwide data survey in Taiwan, Wu et al reported a significant protective effect for individuals who took statins for more than 830 days. 36 In our study, for the continuous statin users, the average time from baseline until diagnosis was 5.8 years.…”
Section: Discussionmentioning
confidence: 70%
“…The interaction between ApoE4 and statin treatment appears to be mixed , but a recent study suggested a beneficial role of simvastatin in slowing the cognitive decline and improving cognitive function in a 10‐year follow‐up of AD patients homozygous for ApoE ε4 . The outcomes and inclusion criteria of enrolled patients differed amongst studies making them hard to compare . A comparison of the effects shown in different study designs identified that the protective effect of statins was reported usually in cross‐sectional but not in longitudinal studies .…”
Section: Medications With Potential Effects On the Brain Cholesterol mentioning
confidence: 99%
“…Seven cohort studies (Chen et al, ; Chuang, Lin, Lin, Sung, & Kao, ; Hendrie et al, ; Hippisley‐Cox & Coupland, ; Li et al, ; C.‐K. Wu et al, ; Yang et al, ) and five case control studies (Booker et al, ; Chen, Liu, Chen, & Wu, ; Corrao et al, ; Horsdal et al, ; Lin et al, ) found that statin use was associated with a reduced risk of dementia. According to these studies, beginning treatment with high doses of lipophilic statins before an early old age (<80 years old) and taking these statins for a long time might reduce the risk of dementia.…”
Section: Resultsmentioning
confidence: 99%